Simulation the Arcitutural Charhacteristic Effect in Increasing the Cooling Needs of Tehran (Case Study: 12 & 22 Region) - reza borna; Nasrin Jafari; Farideh Asadian (تحقیقات کاربردی علوم جغرافیایی)
In order to understand the total consumption of buildings and accurately calculate how much energy each building uses, taking in consideration all the building's lifecycle phases is essential. In order to select the correct methodology for the main study, the researcher began with the determination and the parameters that would have been researched, as well as the analysis and comparison of the different methods used by other researchers to achieve similar goals. The following parameters define the final results and are stabilized or examined to determine their actual effect: A- Constant parameters: 1- Climate data 2- and data on the use of the building: B- variables: 3- Design data: 1- orientation 2- window to wall ratio 3- aspect ratio. This research uses a survey followed by a computer modeling methodology to achieve the goal of providing architects with techniques that reduce energy consumption in building units. To obtain reliable results that are useful to the construction industry in the country, the researcher has ensured that the virtual environment created in the modeling process mimics a typical building environment of Tehran units. Research has shown that passive design techniques have a major impact on the energy consumption of buildings. A significant reduction in consumption (67 percent) was noted when the orientation and percentages of the opening on the wall were changed. In summary, this study has shown that the application of passive, economical and simple design techniques has a major impact on the energy consumption of the unit rooms. If the architects take these ideas into account during the design process, the buildings will take on more responsibility for the environment and consequently reduce carbon dioxide emissions.